Quantitative Transfer Research in Canada: Past Achievements, Current Challenges, and Future Directions - Pizarro Milian, Roger; Zarifa, David (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2021)
The study of transfer in Canadian post-secondary education is a fractured terrain, with vast inter-provincial differences and deep schisms between participating communities. At the time of writing, there exists no comprehensive review that maps the predictors and associated outcomes of transfer in Canada, thus complicating the advancement of this sub-field. Drawing on a review of over 100 academic articles, policy reports, and institutional research documents produced from 1968 to 2020, we discuss the major findings of, methodological approaches to, and gaps within the existing quantitative transfer literature. Further, we outline challenges that Canadian researchers face as they attempt to emulate “best practices” used by internation-al counterparts. In particular, we emphasize the need for the use of more robust administrative data linkages and enhanced methodological sophistication in Canadian quantitative transfer research.